2000
DOI: 10.1016/s0022-5347(05)67516-7
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Radical Nephrectomy: The Cleveland Clinic Experience

Abstract: Retroperitoneoscopy is a reliable, effective and, in our hands, the preferred technique of laparoscopic radical nephrectomy. At our institution retroperitoneoscopy has emerged as an attractive alternative to open radical nephrectomy in patients with T1-T2N0M0 renal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
9

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(110 citation statements)
references
References 14 publications
2
98
0
9
Order By: Relevance
“…The laparoscopic group returned earlier to normal activities, and full recovery was also reached more rapidly. Gill et al [43] compared radical laparoscopic (retroperitoneal) with open nephrectomy in 68 patients (2b). They used an ad hoc questionnaire.…”
Section: Nephrectomy For Malignancymentioning
confidence: 99%
“…The laparoscopic group returned earlier to normal activities, and full recovery was also reached more rapidly. Gill et al [43] compared radical laparoscopic (retroperitoneal) with open nephrectomy in 68 patients (2b). They used an ad hoc questionnaire.…”
Section: Nephrectomy For Malignancymentioning
confidence: 99%
“…reported excellent results in retroperitoneal laparoscopic radical nephrectomy. 8 The average operating time was 2.9 h and estimated blood loss 128 mL. These results were thought to be due to superior technique following a great deal of experience of various kinds of laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…reported that retroperitoneoscopy offered several unique advantages, including expeditious access to the renal artery and vein allowing early ligation, extra fascial mobilization of the kidney and en bloc removal of the adrenal gland, recapitulating the principle of open surgery. 8 Despite these advantages, the technical difficulties have also been debated including the smaller working space of the retroperitoneum and the lack of well-defined anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, retroperitoneal LRN for T1 RCC offered several advantages, with statistical differences from open surgery. Reports worldwide confirm the benefits of this less invasive procedure and comparisons between LRN and open RN have consistently shown advantages for the former approach in all indices of perioperative morbidity, including estimated blood loss, postoperative narcotic requirement, length of hospitalization and duration of convalescence [6,7,[11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%